(3eTcdGJ GdETGQGJs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3hHYO , fMh Ndb eNJdaI HMSH GdeYOfjGJ hGdfHGJ hGdMjhGf CLfGSgG hCfhGYgG s
(3BNQgG (B:s
(3hCfG CJhbY eef jbY Edjg cJGHi gPG Cf jUdM eG jYKQ Ydjg ef GdMdd hGdaSGO s
(3HgG fXGe GdJYbjHIs
(3fSNI NGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdadSaI hGdefWbs